Eficácia do Programa de Enriquecimento Instrumental-PEI, versão básica, em crianças com transtornos do neurodesenvolvimento (TDAH e Dislexia) - Ricci, Karen Alves (2016)
Feuerstein's Instrumental Enrichment (FIE), by Reuven Feuerstein, aims to increase the level of cognitive modifiability and learning ability, but the research about the efficacy of FIE basic version in neurodevelopmental disorders is still scarce. This research addressed two specific neurodevelopmental disorders, the Attention deficit hyperactivity disorder (ADHD), characterized by harmful levels of inattention, disorganization and / or hyperactivity-impulsivity; and developmental dyslexia, specific learning disorder with impairments in reading, characterized by specific deficits in individual ability to perceive and process academic information efficiently and accurately. In this sense, the objective was to verify the efficacy of FIE, basic version, in children with ADHD and dyslexia. To do this, 22 elementary school children from public and private institutions, with a previous diagnosis of neurodevelopmental disorder, particularly ADHD and Dyslexia, participated in the study. From the 22 participants, 11 children were allocated semi-randomly in the experimental group and 11 children in the control group. A battery of neuropsychological tests with the following instruments was applied: Computerized Dynamic Test of Inductive Reasoning for Children; Raven Progressive Matrices; Wechsler Intelligence Scale for Children- WISC-IV (estimated IQ); Trail Making Test A and B; Trails Making Test for preschoolers; Semantics Stroop Test; Executive Function and Children Regulation Inventory; Words and Pseudowords Repeating Test; Infant Nomination Test and Rey Complex Figure Test. For the intervention, the experimental group was divided into four groups, two groups of children diagnosed with ADHD and two groups of children diagnosed with dyslexia. The intervention sessions with FIE occurred in 21 to 26 sessions depending on group, the last quarter of the school year, in twice a week meetings of 50 minutes each. After it was verified that not all the distributions followed the standard of normality, Mann-Whitney U non-parametric analyzes were conducted to compare the differences between the pre-and-post-test in the experimental and control groups and, afterwards, the Cohen's d effect size. The results revealed significant effect on the Rey Complex Figure Test in copy, and the Trail Making Test part B in which the experimental group presented higher gains. In the naming part of the Stroop Test, the control group presented higher gains. Although there were no significant differences in most of the evaluated measures, there was an increase in the scores of the intervention group compared to the control group in most of the measures. The effect size, by Cohen's d, was small to moderate for most measures. We concluded that the FIE, basic version, is tool to be used with ADHD and dyslexic children, however more research is necessary. Although the results show few significant effects, the effect sizes analysis may have practical implications, revealing the importance of intervention for children with neurodevelopmental disorders.